Assertive Community Treatment for Patients with Schizophrenia - Monika Lukut; Agustina Konginan (Jurnal Psikiatri Surabaya, 2023)
AbstractsIntroductions: Schizophrenia is a long-term, severe mental disorder involving a breakdown in the relation between thought, emotion, and behavior, leading to faulty perception, inappropriate actions and feelings, withdrawal from reality and personal relationships into fantasy and delusion, and a sense of mental fragmentation. Methods: The treatment of schizophrenia requires a holistic approach such as psychopharmacology therapy and psychosocial rehabilitation. The combined treatment has some advantages compared to medication alone. Assertive Community Treatment is one of the psychosocial rehabilitation. It is a healthcare program with multidisciplinary approaches and team members. Results: They have got to work as a team to provide intensive care to patients with severe mental disorders. They serve to treat the patient holistically in the patient’s environment rather than in the hospital. Conclusions: Some studies showed that Assertive Community treatment could reduce hospitalization, improved the quality of life of patients, and reduced the symptoms experienced by the patients.